The growzen™ buddy smartphone app to improve adherence in patients receiving recombinant human growth hormone therapy: a retrospective observational study in Argentina - van Dommelen, Paula; Arnaud, Lilian; Assefi, Aria Reza; Crespo, Maria Lourdes; Debicki, Matias; Michelis, Fulvio; Koledova, Ekaterina (Frontiers in Endocrinology, 2024)
Introduction This study in Argentina evaluated the impact of the growzen™ buddy smartphone app on adherence to recombinant human growth hormone (r-hGH) treatment. Methods The adherence data, invitation dates with a link to the app, app activation dates, and height measurements entered were extracted from the growzen™ digital health ecosystem. Patients with 12 months of adherence data, aged ≥2 years at treatment start, and aged <19 years were selected both before and after app implementation. Mean adherence was classified as optimal (≥85%) versus suboptimal (<85%). Adherence before and after implementation and the pre–post effect on adherence were assessed. Results Data for 830 patients were available. Prior to app implementation, the proportion of patients with optimal adherence was 68% (n = 348/515). Following the app implementation, out of 315 patients, 302 (96%) received an invitation with a link to the app, 225 (71%) activated their account, and 127 (40%) entered height data in the first year. There was a significant early increase in the proportion of patients with optimal adherence following implementation: 82% (n = 258/315), p < 0.001. After implementation, the proportion of patients with optimal adherence included 80% (n = 78/98) of those with an active account who did not enter height measurements and 89% (n = 113/127) of those who did. There was a significant and positive pre–post app effect on adherence (p < 0.01) in patients with an active account. Discussion Our results show that using the growzen™ buddy app has a rapid and positive impact on adherence to r-hGH treatment, and patients who were more engaged with the app demonstrated better adherence.